Assessment of effectiveness of health education bundle to overcome vaccine hesitancy in mothers: single blinded randomized study - Mounika Bazar; Kiran N. Baliga; Anupama Nayak Panakaje; S. R. Ravikiran (BMC Research Notes)
Abstract Objective Vaccine Hesitancy (VH) challenges previously perceived attitudes of a simple dichotomy of “accept” or “reject”. This is not just due to people being uninformed or misinformed but rather due to multiple forms of distrust. It is criticized as a vague notion with an uncertain hypothetical background. Therefore, this study aimed to assess the baseline knowledge and immunization practices of postnatal mothers and their hesitancy after intervention with the health education tool ‘SuBaDRa’ and compare it with those of the control group. Result This hospital-based, single-blinded randomized control study was performed for 2 years with 272 (136 per group) postnatal mothers (booked cases with immunization cards and access to a smartphone) in Karnataka, India. 'SuBaDRa', a tailored health education tool, was used to counsel the intervention group: Presenting Sustainable initiatives by the government; assessing mothers' Baseline immunization knowledge and postintervention revaluations via the 'WHO SAGE questionnaire’, Dissipating knowledge via health education and Reinforcement with social media applications. The control group was counseled about essential newborn care. The vaccine delay of infants at birth and at 6, 10, and 14 weeks and 9 months of age was assessed. The secondary outcome measures mothers' attitudes toward immunization postintervention. The vaccine was considered delayed if it was received later than 2 weeks after the recommended age. The characteristics of the study subjects, i.e., postnatal mothers with eligible newborns, were analyzed via descriptive statistics. These characteristics were compared between the intervention and control groups via the Chi-square (χ2) test and Fischer’s exact test. The results revealed that the intervention group vaccine delays at 6, 10, 14 weeks and 9 months were 5.9%, 3%, 0.7% and 11.9%, respectively, and the control group vaccine delays were 20%, 28.9%, 55.6% and 48.1%, respectively, with p values of 0.001 at 6 weeks and 0 for the rest, all of which were highly significant. Trial registration The study was registered on Clinical Trials Registry – India (CTRI) with the registration number (CTRI/2021/08/035749), registered on (18/08/2021).